The Transformation of Balinese Satua Values: Strengthening the Character Education of the Alpha Generation: (A Case study at Saraswati Tabanan Kindergarten, Bali) - Adhi, Made Kerta; Parmini, Ni Putu; Wulandari, Ni Putu Desi (SCAD Independent, 2020)
The study aims at describing the transformation of the Balinese satua values for strengthening the alpha generation (Gen A)’s character education in Kindergarten Saraswati Tabanan. The method used was qualitative research with a Cultural Studies approach. The results showed that Masatua (storytelling) was carried out for twenty minutes every “Thursday Cultures